PEMBERIAN TUGAS TERSTRUKTUR YANG DIPRESENTASIKAN DAPAT MENINGKATKAN PRESTASI BELAJAR SISWA TENTANG PERKEMBANGAN MASYARAKAT ISLAM INDONESIA PADA SISWA KELAS VII SMPN 3 KEPENUHAN - Sikumbang, Hotnida (Edu Research, 2017)
This study aims to reveal the influence of structured learning tasks presented to the social learning achievement, and to express the learning of structured tasks presented can influence the motivation to learn social knowledge of the seventh grade students of SMPN 3 Kepenuhan. This research uses action research for three rounds. Each round consists of four stages: design, activity and observation, reflection, and revision. Target of this research is student of Class VII SMPN 3 Kepenuhan. Data obtained in the form of formative test results, observation sheet of teaching and learning activities. From the analysis result got that student's learning achievement have improvement from Pre cycle until cycle I and cycle II that is, cycle I (10%), cycle II (70%), cycle II (100%). So it can be concluded that from this study structured method of learning tasks presented with a positive influence on student motivation of class VII SMPN 3 Kepenuhan.